2023
DOI: 10.1093/humrep/deac267
|View full text |Cite|
|
Sign up to set email alerts
|

Association between body mass index, weight loss and the chance of pregnancy in women with polycystic ovary syndrome and overweight or obesity: a retrospective cohort study in the UK

Abstract: STUDY QUESTION What are the associations between baseline BMI (Study 1) and change in body weight (Study 2) with the likelihood of pregnancy in women with polycystic ovary syndrome (PCOS). SUMMARY ANSWER In women with PCOS, higher baseline BMI was associated with a lower chance of pregnancy; however, weight loss was associated with an increased chance of pregnancy versus maintaining a stable weight or gaining weight. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…In the USA, 69% of women with PCOS are obese and 64% have metabolic syndrome [1,2]. Weight loss improves both metabolic and reproductive outcomes in PCOS [3][4][5][6]. Our earlier research in women without PCOS demonstrated that replacement of dietary fat with carbohydrates (CHOs) can lead to weight loss in free-living conditions [7].…”
Section: Introductionmentioning
confidence: 99%
“…In the USA, 69% of women with PCOS are obese and 64% have metabolic syndrome [1,2]. Weight loss improves both metabolic and reproductive outcomes in PCOS [3][4][5][6]. Our earlier research in women without PCOS demonstrated that replacement of dietary fat with carbohydrates (CHOs) can lead to weight loss in free-living conditions [7].…”
Section: Introductionmentioning
confidence: 99%
“…In the USA 69% of women with PCOS are obese and 64% have metabolic syndrome [1,2]. Weight loss improves both metabolic and reproductive outcomes in PCOS [3][4][5][6]. Our earlier research in women without PCOS demonstrated that replacement of dietary fat with carbohydrates (CHO) can lead to weight loss in free-living conditions [7].…”
Section: Introductionmentioning
confidence: 99%